Rituximab Treatment in a Patient with Active Graves’ Orbitopathy and Psoriasis - Şimşek, Tülay (Turk J Ophthalmol, 2017)
Management of Graves’ orbitopathy remains an important therapeutic challenge. Current therapeutic modalities are unsatisfactory in about one third of patients. Rituximab is a monoclonal antibody against CD20 antigen that is expressed in mature and immature B cells. Early experience with rituximab suggests that it is a promising alternative therapy for Graves’ orbitopathy. Here we report a case of a 49-year-old woman with Graves’ orbitopathy and psoriasis. The patient received 2 infusions of 1 g rituximab 2 weeks apart. Although there was improvement in inflammatory signs of the disease, proptosis did not change after the treatment.